2020
DOI: 10.1073/pnas.2001776117
|View full text |Cite
|
Sign up to set email alerts
|

Elevated energy requirement of cone photoreceptors

Abstract: We have used recent measurements of mammalian cone light responses and voltage-gated currents to calculate cone ATP utilization and compare it to that of rods. The largest expenditure of ATP results from ion transport, particularly from removal of Na+ entering outer segment light-dependent channels and inner segment hyperpolarization-activated cyclic nucleotide-gated channels, and from ATP-dependent pumping of Ca2+ entering voltage-gated channels at the synaptic terminal. Single cones expend nearly twice as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 44 publications
(52 reference statements)
1
70
0
Order By: Relevance
“…In addition, a previous study showed that lipids might be an alternative energy source for cones by β-oxidation (Joyal et al, 2016). It is likely that cones can use these alternative fuels to meet their intense energy demands (Ingram et al, 2020) (Fig. 6,7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, a previous study showed that lipids might be an alternative energy source for cones by β-oxidation (Joyal et al, 2016). It is likely that cones can use these alternative fuels to meet their intense energy demands (Ingram et al, 2020) (Fig. 6,7).…”
Section: Discussionmentioning
confidence: 96%
“…The results above suggest that Txnip may prolong RP cone survival by enhancing lactate catabolism via Ldhb, which may lead to greater ATP production by the oxidative phosphorylation (OXPHOS) pathway. Cone photoreceptors are known to require high levels of ATP to maintain their membrane potential, relying primarily upon the Na + /K + ATPase pump (Ingram et al, 2020). To investigate whether Txnip affects the function of the Na + /K + pump in RP cones, freshly explanted P20 rd1 retinas were treated with RH421, a fluorescent small-molecule probe for Na + /K + pump function (Fedosova et al, 1995).…”
mentioning
confidence: 99%
“…Consequently, rods are more often hyperpolarized than cones despite the same light exposure 29 . Cones are suspected to have increased metabolic demands to maintain the default depolarized state 29 , 30 , which aligns with their higher glycogen stores 31 . Furthermore, changes in glucose level and inhibition of glycolysis affect rods more than cones, suggesting that rods may depend more on glycolytic metabolism than cones 32 34 .…”
Section: Photoreceptor Metabolic Demandsmentioning
confidence: 99%
“…Therefore, vertebrate photoreceptors need to maintain a large inward cation current in darkness, which dominates their energy consumption. As light closes CNG channels, increasing ambient illumination decreases the energy consumption of photoreceptors (Linsenmeier and Braun, 1992 ; Okawa et al, 2008 ; Ingram et al, 2020 ) whereas higher concentration of odors would be expected to increase energy expenditure in OSNs.…”
Section: Vertebrate Transduction Cascadesmentioning
confidence: 99%